Coastal Restoration Based on Institutional Approach: A case study in the city of Probolinggo, East Java Province, Indonesia - ., Rudianto (Advances in Social Sciences Research Journal, 2017)
The coastal area in Indonesia is currently experiencing a very heavy pressure, whether caused by human activities, or caused by natural processes. Damage to coastal ecosystems like mangroves, coral reefs, sea grass beds, estuaries and the region has reached at an alarming rate. It is estimated that more than 41 percent of the coastal area in Indonesia is experiencing environmental degradation. This leads to the coastal region can no longer support the region’s ecological system. Associated with more severe coastal damage, it is necessary efforts to save the coast through the people residing in coastal areas as a subject of coastal development. In this regard, more comprehensive studies are needed to determine the institutional aspects as an effective solution for dealing with coastal restoration.The aim of this research is to handle of coastal environmental damage by coastal restoration based on institutional aspect, and to formulate institutional models in accordance with local wisdom. Therefore, it is needed a statistical approach with assumption that there is relationship between restoration of mangrove with institutional aspect. Partial Least Square (PLS) is used to examine such relationship. To analyse priority of institutional strategy, it is used SWOT analysis.The result of this research is that to overcome the damage of mangroves, it is necessary to formulate activities synergy among local government, private and local people. Therefore, Co-management approach is needed to strengthen mangrove Community Working Group. (CWS).